Mother's psychology and exclusive breastfeeding success: Scoping review - Kusteja, Nadya Fauzia; Nurfitriyani, Ela; Aprianti, Nurul Azmi; Adnani, Qorinah Estiningtyas Sakilah (Institute of Computer Science (IOCS), 2024)
According to the World Health Organization (WHO) definition in 2011, exclusive breastfeeding means providing only breast milk without any other food or drink to the baby from birth to six months of age, except for medications and vitamins. This does not imply that breastfeeding should stop after the six-month period. Instead, breastfeeding should continue until the child reaches two years of age. Breast milk is recognized as the initial, primary, and best food for infants, based on scientific principles. This study aims to identify the relationship between the psychological state of breastfeeding mothers and the success rate of exclusive breastfeeding. This study employs a scoping review method involving the search, screening, and synthesis of literature pertinent to the research topic. The steps involve formulating the research question, setting inclusion and exclusion criteria, conducting literature searches, and selecting relevant literature, data extraction, and qualitative analysis. Psychological factors in mothers, such as high breastfeeding self-efficacy, and the absence of postpartum depression and anxiety, are significantly linked to the success of exclusive breastfeeding. Psychological interventions are needed to support the success of exclusive breastfeeding. Positive psychological factors in mothers, including high breastfeeding self-efficacy and the absence of postpartum depression and anxiety, play a crucial role in supporting the success of exclusive breastfeeding. Interventions to improve the psychological condition of breastfeeding mothers should be implemented to increase the rates of exclusive breastfeeding. Further research is needed to explore the psychological factors influencing the success of exclusive breastfeeding.